Genetic Addiction Risk Score (GARS): Testing For Polygenetic Predisposition and Risk to Reward Deficiency Syndrome (RDS) - Blum, Kenneth; Fornari, Frank; Downs, B.William; Waite, Roger L.; Giordano, John; Smolen, Andrew; Lui, Yijun; Tain, Jai; Majmundar, Neil; Braverman, Eric R. (IntechOpen, 2011)
None